[Comment] Long term oncological outcomes for laparoscopic versus open surgery for rectal cancer-a population-based na tionwide noninferiority study - Tang Bin (结直肠肛门外科)
[Aim] The aim of this work was to compare the 5-year overall survival in a national cohort of patients undergoing curative abdominal resection for rectal cancer by laparoscopic (LAP) or open (OPEN) surgery. [Method] All patients diagnosed with clinical Stage I-III rectal cancer and who underwent LAP or OPEN abdominal curative surgery in Sweden between 2010 and 2016 were retrieved from the Swedish Colorectal Cancer Registry. A noninferiority study design was employed with a statistical power of 90%, a one-side type I error of 2.5% and a noninferiority margin of 2%. The analyses were performed as intention-to-treat and the relationship between surgical technique and overall mortality within 5 years was analysed. Multilevel regression models with the patients matched by propensity scores adjusted for patient- and tumour-related variables were used. [Results] A total of 8410 Stage I-III cancer patients were included. This group underwent 2094 LAP (24.9%) and 6316 OPEN (75.1%) procedures and were followed until 31 December 2020. Multivariable Cox regression demonstrated that 5-year overall survival was higher in the LAP group [hazard ratio (HR) 0.877; 95% CI 0.775-0.993]. [Correction added on 21 November 2022, after first online publication: In the preceding sentence, the CI value for LAP group has been corrected from "0.877" to "0.775" in this version.] The outcome was similar when multiple imputation and propensity score matching were employed. When cT4 patients were excluded there was no difference (HR 0.885; 95% CI 0.790-1.033). At 5-years' follow-up local recurrence was not different, at 2.9% for the LAP group and 3.6% for the OPEN group (p = 0.075), while metastatic disease was more frequent in the OPEN group (19.6% compared with 15.6% for LAP; p < 0.001). [Conclusion] This study demonstrated that the LAP technique was not inferior to OPEN surgery with regard to overall 5-year survival. These results support the use of laparoscopic surgery.